2010
DOI: 10.1017/s0043933910000085
|View full text |Cite
|
Sign up to set email alerts
|

Comparative aspects of Fusarium mycotoxicoses in poultry fed diets containing naturally contaminated grains

Abstract: Fusarium mycotoxins are structurally diverse chemically distinct groups of fungal metabolites which are prevalent globally. Economically important Fusarium mycotoxins include trichothecenes, zearalenone and fumonisins. Deoxynivalenol (DON, vomitoxin), and its acetylated forms, are the most commonly encountered trichothecenes in grains used for poultry feeds. Early experiments, conducted for short periods or using single purified compounds, showed that poultry were resistant to DON. More recent experiments, uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 54 publications
(38 reference statements)
0
4
0
2
Order By: Relevance
“…The most common mycotoxins found in grains for poultry feed are deoxynivalenol (DON) and its derivatives. [ 42 ]. In the studies presented, DON was identified at a poultry farm (VIII) at a concentration of 151.2 mg/kg dust.…”
Section: Resultsmentioning
confidence: 99%
“…The most common mycotoxins found in grains for poultry feed are deoxynivalenol (DON) and its derivatives. [ 42 ]. In the studies presented, DON was identified at a poultry farm (VIII) at a concentration of 151.2 mg/kg dust.…”
Section: Resultsmentioning
confidence: 99%
“…A recent global survey of mycotoxins in feed (1,384 samples) indicated that the trichothecene deoxynivalenol (DON) was the most prevalent mycotoxin, with 79% of the samples testing positive at an average concentration of 0.6 mg/kg and a maximum concentration of 8.4 mg/kg ( Kosicki et al., 2016 ). Deoxynivalenol is consistently the most predominant mycotoxin in Fusarium -infected grains in Canada ( Tittlemier et al., 2013a , Tittlemier et al., 2013b ) and often co-contaminates with other trichothecenes, such as 3-acetyl DON (3ADON) and/or 15-acetyl DON (15ADON) ( Girgis and Smith, 2010 , Maresca, 2013 , Miller and Richardson, 2013 ). Fusarium mycotoxins induce a wide range of adverse effects in food-production animals with symptoms ranging from vomiting and feed refusal to estrogenic effects and reduced performance, depending on the toxin and sensitivity of the animal species ( Osweiler, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Pour les mycotoxines, des normes (directive 2002/32/CE) et des recommandations (2006/576/CE) existent en UE pour les aflatoxines et certaines fusariotoxines. Les relations entre mycotoxinesdose-effets-espèce-âge ne sont pas clairement établies dans bien des cas (Leeson et al 1995, Girgis et Smith 2010. Dans l'ensemble, le poulet semble peu sensible aux fusariotoxines (DON, zéaralénone, moniliformine) naturellement retrouvées dans les céréales et leurs coproduits (Girgis et Smith 2010).…”
Section: C) Toxicité Due à La Qualité Dégradée Des Matières Premièresunclassified
“…Les relations entre mycotoxinesdose-effets-espèce-âge ne sont pas clairement établies dans bien des cas (Leeson et al 1995, Girgis et Smith 2010. Dans l'ensemble, le poulet semble peu sensible aux fusariotoxines (DON, zéaralénone, moniliformine) naturellement retrouvées dans les céréales et leurs coproduits (Girgis et Smith 2010). Toutefois, un lien a été reporté avec la dyschondroplasie (Whitehead 1998).…”
Section: C) Toxicité Due à La Qualité Dégradée Des Matières Premièresunclassified